Stock return movements of companies affiliated with Danantara - Hidayatulloh, Ivan Wahyu (Jurnal Ekonomi Indonesia, 2026)
This study examines the stock return movements of ten companies affiliated with the Danantara sovereign wealth fund in the Indonesian stock market, focusing on inter‑issuer relationships and linkages with the JKSE. We employ an empirical VAR(1) framework, Granger-Causality, variance decomposition and price forecasts (sample: 966 observations, approximately four trading years). The main findings indicate that idiosyncratic risk predominates in explaining each stock's variance, while the JKSE consistently appears as the second‑largest external contributor. VAR(1) estimates reveal only limited lagged relationships, with some significant negative effects of R_JKSE(−1) on several variables. Price forecasts show heterogeneous performance, some variables appreciate while the majority decline; the average price of the ten stocks declined by 4.9576% over the study horizon. The implications suggest that Danantara needs to re-evaluate the companies it has acquired, as not all of them exhibit projected stock-price gains and some display correlations. In addition, further academic research should be conducted after several post-acquisition periods to assess longer-term impacts.